Printed wire assembly HASS profile development based on HALT. (July 2020) - Awad, Mahmoud I.
Abstract: Highly accelerated life testing (HALT) is a test method used to expose design weaknesses at early stages of product development cycle by testing products under elevated stresses. Similarly, highly accelerated stress screening (HASS) is a widely accepted production test derived from HALT used to detect manufacturing defects jeopardizing product reliability. Despite wide usage of HASS, there is no clear way of deriving HASS from HALT for printed wire assemblies (PWA). Practitioners develop HASS by experimenting with 50% of HALT shock loads and 80% of thermal limits then reduce shock level until PWA pass at least twenty profiles. Such process is cost and time consuming. In this article, a more efficient and safe method to plan HASS is proposed and demonstrated using a real life case study. Successful implementation of the proposed method will enable practitioners to predict and determine how many profiles a PWA can survive under different loading conditions, which will reduce testing, time and cost. The proposed method is derived from the physics of failure and statistical modeling of solder joint strain range. The physical basis of the model is provided by Minor's rule of damage accumulation and Coffin-Manson and Basquin total strain model. Strain amplitude of solder joint is modeled using a power model in terms of vibration load and temperature. The proposed method is demonstrated using a gauge acquisition PWA used for oil & gas equipment. Results of case study suggest that proposed method is able to predict number of HASS profiles to failure with reasonable 3% prediction error. Highlights: Despite wide usage of HASS, there is no clear way of deriving HASS from HALT for printed wire assemblies (PWA). In this article, a more efficient and safe method to plan HASS is proposed and demonstrated using a real life case study. Such process is cost and time consuming. In this article, a more efficient and safe method to plan HASS is proposed and demonstrated using a real life case study. Successful implementation of the proposed method will enable practioners to predict and determine how many profiles a PWA can survive under different loading conditions, which will reduce testing, time and cost. The method utilizes SJ physics of failure along with Miner''s cumulative damage rule to determine the appropriate HASS vibration level.